Exophytic Gastrointestinal Stromal Tumor with Cystic Changes in the Pancreas - Dr Juily Aher, Dr. Jaini Modi, Dr. Vikrant Bhagvat, Dr. Abhishek Mondal, Dr Anurag Dandekar (International Journal of Innovative Research in Medical Science, 2017)
The term stromal tumor was coined in 1983 by Clark and Mazur for smooth muscle neoplasm of the gastrointestinal tract (GIT). Gastrointestinal stromal tumors (GIST) are nonepithelial tumors arising from the interstitial cells of Cajal, which express KIT protein-CD117 on immunohistochemistry. GIST can arise anywhere in the GIT, including the mesentery, omentum, and retroperitoneum. We present a case of multiple stomach gist with cystic changes in the pancreas.